If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -36p = -6 Solving -36p = -6 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '-36'. p = 0.1666666667 Simplifying p = 0.1666666667
| -16t^2+48=0 | | 8c-9=40.6 | | -21=7(w-5) | | 3a+5-6a=26 | | 25-2y=7 | | 7-x-3x=-33 | | 1a*1=2 | | 3-8n=-4n+15 | | p^2+14+40=0 | | 4.9t^2-10t-45=0 | | -(1-9x)-10= | | 1-4y+8=0 | | 2p-1.4=-8p-14.9 | | 3c-7=5c+9 | | (n+8)+(n+-12)= | | 5x^3-19x^2+4x=32 | | 2+7x=4x+-2 | | 5(t-3)-2=-30 | | 14-z=2 | | 1+12(x-5)= | | 2m+-1nx=x+4 | | 5x^3+45=2x^2+18 | | 7x-6-3x=6x-5 | | 12+2b=60 | | -2p+8=5p-10 | | 60+50.4x=57.95x | | 3n+3=61 | | 8x+9=5x-29 | | 12(d+2)=3(d-8)+9d | | w-2w=4w+20 | | -13=-5a-(-12) | | 6x-3=-87 |